Preparation method and application of biomimetic mineralized hydrogel coating with strong adhesiveness

By preparing a bionic mineralized hydrogel coating with strong adhesion on the surface of the bone implant, the problems of complex preparation process, long periods and insufficient binding performance of the coating and substrate in the prior art are solved, and more stable and Efficient surface modification of bone implants.

CN119455116AActive Publication Date: 2025-02-18NORTHWESTERN POLYTECHNICAL UNIV

Patent Information

Application Number
CN202411430763.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-02-18
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

The existing hydrogel coating modification technology on the surface of bone implants has problems such as complex preparation process, long periods and insufficient bonding performance of the coating and substrate.

Method used

A method of preparing a highly adhesion bionic mineralized hydrogel coating, including pretreating the surface of the bone implant body and immersing it in a polyvinyl alcohol solution, performing a single freeze-thaw cycle and annealing treatment, and then alternately immersing it in the containing Surface mineralization is performed in calcium and phosphorus-containing solutions to induce the formation of a uniform hydroxyapatite coating.

Benefits of technology

The stability and adhesion properties of the coating are significantly improved, the mineralization time is shortened, and a uniformly deposited hydroxyapatite coating is formed, which enhances the interface binding performance between the bone implant and the bone tissue.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455116A_ABST
    Figure CN119455116A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a biomimetic mineralized hydrogel coating with high adhesiveness, and relates to the technical field of bone implant surface modification. The method comprises the following steps: immersing a bone implant subjected to surface pretreatment into a polyvinyl alcohol solution, then carrying out single freezing and thawing cycle, and then carrying out annealing treatment, alternately soaking the annealed bone implant in a calcium-containing solution and a phosphorus-containing solution, and carrying out surface mineralization treatment; then, inducing a product subjected to surface mineralization treatment to obtain hydroxyapatite; the biomimetic mineralized hydrogel coating with strong adhesiveness is obtained on the surface of the bone implant. According to the method, the surface of the bone implant is coated with the strong-adhesion hydrogel coating by adopting a dip-coating method, and the thickness and the surface flatness of the coating can be controlled by adjusting the dip-coating frequency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of bone implant surface modification, and in particular to a preparation method and application of a bionic mineralized hydrogel coating with strong adhesion. Background Art

[0002] At present, orthopedic implant materials mainly include ceramics, polymers, metals and composite materials. Among them, biomedical metal materials have become the most widely used bone implant materials due to their excellent mechanical properties and machinability. Traditional medical stainless steel has low cost, superior mechanical properties and good corrosion resistance, but local corrosion is easy to release harmful metal ions or fragments, which poses potential harm to the human body and requires surface protection. Titanium and its alloys have high strength, good corrosion resistance and excellent biocompatibility, and are widely used in orthopedic and dental implants. However, its high elastic modulus is prone to stress shielding effect, causing implant loosening and infection risks. The biological inertness of titanium alloys also limits the improvement of its bone integration and antibacterial properties. Second-generation bone implant materials, such as polyetheretherketone (PEEK), have become emerging bone implant materials because of their elastic modulus close to that of cortical bone and their excellent wear resistance, radiotransparency and biocompatibility. However, the biological inertness of PEEK hinders its effective integration with bone tissue, limiting its clinical application. Current research mainly focuses on surface modification and the addition of active materials to enhance the bioactivity and compatibility of PEEK. Although existing technologies have improved the performance of metal and polymer implant materials to a certain extent, how to achieve stronger bioactivity and antibacterial effects while ensuring the excellent mechanical properties of the materials is still a major challenge in the research of bone implant materials. Therefore, the development of biomimetic mineralized coatings with stronger adhesion and bioactivity to improve the interfacial bonding performance between bone implant materials and bone tissue has become a key technical direction to promote clinical applications in this field.

[0003] Hydrogels have broad application prospects in the field of tissue engineering due to their unique adjustable mechanical properties and excellent biocompatibility. By introducing inorganic minerals such as calcium-phosphorus compounds or calcium carbonate, the prepared hydrogels have good bone induction ability while maintaining the mechanical properties of the hydrogels, thereby significantly enhancing the application value of the hydrogels in the field of bone tissue engineering. At present, the preparation methods of mineralized hydrogels mainly include immersion method and in situ mineralization method, but these methods have some limitations. For example, the Chinese patent (CN107778416A) immerses acrylonitrile / vinyl imidazole hydrogel in a mixed solution of calcium chloride and sodium dihydrogen phosphate by immersion method, so that calcium ions and phosphate ions diffuse into the gel matrix, and then adjusts the pH value by ammonia water to promote the mineralization reaction to form a mineralized hydrogel. However, the mineralization time of this method is as long as 24 to 48 hours, and the coating preparation efficiency is low. The Chinese patent (CN112625158A) uses polyacryloyl glycinamide hydrogel containing alkaline phosphatase to carry out mineralization reaction in triethanolamine solution of calcium glycerophosphate. This process relies on photoinitiators and the preparation of calcification solution is complicated. The calcification time is as long as 3 to 10 days. In addition, the Chinese patent (CN114432275A) mixes hydrogel material, initiator of cross-linked polymer and initiator of cross-linked polymer to prepare prepolymer and dry it in an oven after vacuum treatment to obtain a high-adhesion analgesic hydrogel microneedle patch. However, this method is complicated and has many restrictions on hydrogel materials, narrow applicability, and complicated preparation process, which affects the flexibility of subsequent drug loading.

[0004] In summary, the existing hydrogel coating modification technology on the surface of bone implants faces problems such as complex preparation process, long cycle and insufficient bonding performance between coating and substrate. Therefore, developing a hydrogel coating with simple preparation, strong adhesion and biomimetic mineralization properties is of great significance to enhance the clinical application potential of bone implants. Summary of the invention

[0005] In view of the deficiencies in the above-mentioned background technology, the present invention mainly solves the problems of poor biological activity on the surface of existing bone implants, weak adhesion of modified coatings, and poor osteogenesis. The present invention provides a preparation method and application of a biomimetic mineralized hydrogel coating with strong adhesion. The composite coating prepared by the method can form strong adhesion with the base material, significantly improve the stability of the coating, and provide a simple biomimetic mineralization method to shorten the mineralization time, forming a uniformly deposited hydroxyapatite coating on the surface of the bone implant.

[0006] The first object of the present invention is to provide a method for preparing a biomimetic mineralized hydrogel coating with strong adhesion, comprising the following steps: The surface pretreated bone implant was immersed in a polyvinyl alcohol solution and then subjected to a single freeze-thaw cycle, followed by an annealing treatment; The annealed bone implant is alternately immersed in a calcium-containing solution and a phosphorus-containing solution to perform surface mineralization treatment; the product after the surface mineralization treatment is then induced to become hydroxyapatite; that is, a bionic mineralized hydrogel coating with strong adhesion is obtained on the surface of the bone implant.

[0007] Preferably, the surface mineralization treatment includes: The annealed bone implant is immersed in a phosphorus-containing solution for 2 to 4 minutes, then rinsed in deionized water for 10 to 15 seconds, immersed in a calcium-containing solution for 2 to 4 minutes, and rinsed in deionized water for 10 to 15 seconds, and the cycle is repeated 3 to 6 times.

[0008] Preferably, the phosphorus-containing solution is a dipotassium hydrogen phosphate solution with a concentration of 200-400 mM; The calcium-containing solution is a calcium chloride solution with a concentration of 300-600 mM.

[0009] Preferably, the product after the surface mineralization treatment is induced to become hydroxyapatite, comprising: The surface mineralized bone implant is immersed in a calcium chloride solution for 24 to 36 hours to induce the surface mineralized product to become hydroxyapatite; Among them, the calcium-phosphorus ratio in hydroxyapatite is 1.60~1.75, and the particle size is 300~500 nm.

[0010] Preferably, before the surface mineralization treatment, the method further comprises: soaking the annealed bone implant in a 1 M Tris buffer solution with a pH of 9 for 12 to 24 hours.

[0011] Preferably, the process of immersing the surface pretreated bone implant into the polyvinyl alcohol solution comprises immersing the bone implant into the polyvinyl alcohol solution at least once; wherein each immersion process is to immerse the surface pretreated bone implant into the polyvinyl alcohol solution, ensure that no bubbles are generated on the surface, and then take it out and place it in an oven to dry for 10 to 15 minutes; The bone implant after surface pretreatment is immersed in a polyvinyl alcohol solution and then left to stand at room temperature for 0.5 to 1 hour; wherein the concentration of the polyvinyl alcohol solution is 10 to 12 wt %.

[0012] Preferably, a single freeze-thaw cycle comprises: immersing the surface pretreated bone implant in a polyvinyl alcohol solution, freezing it at -20 to -18°C for 8 to 10 hours, and then thawing it at room temperature for 2 to 4 hours.

[0013] Preferably, the annealing temperature is 100-110° C., and the annealing time is 90-120 minutes.

[0014] The second object of the present invention is to provide a biomimetic mineralized hydrogel coating with strong adhesion, which is prepared by the above method, wherein the thickness of the biomimetic mineralized hydrogel coating with strong adhesion is 15-23 μm, and the interface toughness can reach 208.54 J / m 2 .

[0015] The third object of the present invention is to provide a biomimetic mineralized hydrogel coating with strong adhesion for use in bone implants.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a preparation method and application of a biomimetic mineralized hydrogel coating with strong adhesion. By annealing, the formation of ordered nano-crystal domains inside the hydrogel and surface hydrogen bonds is induced, thereby improving the adhesion performance of the coating; the hydroxyapatite on the surface after biomimetic mineralization is beneficial to the proliferation and adhesion of surface osteoblasts, thereby promoting the repair of bone tissue.

[0017] The present invention adopts annealing treatment to increase the cross-linking degree of the hydrogel, and the coating has a smooth appearance and excellent adhesion performance.

[0018] The invention provides a method for preparing a mineralized hydrogel coating, which has a simple process, cheap raw materials and a short preparation time, and forms a uniform hydroxyapatite coating on the surface of the hydrogel. The method is applicable to a variety of bone implant materials and is conducive to industrial production.

[0019] The invention adopts a dipping method to coat a strong adhesion hydrogel coating on the surface of a bone implant, and the thickness and surface flatness of the coating can be controlled by adjusting the number of dipping times.

[0020] The present invention regulates the immersion time of the mineralization solution, and can control the thickness and distribution of the mineralization coating, thereby regulating the biological performance of the bone implant.

[0021] The present invention adopts plasma treatment or sulfonation treatment to pretreat the bone implant material, increases the surface active groups of the bone implant through the pretreatment, and improves the material modification effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a scanning electron microscope image of the surface coating morphology of the strongly adhered biomimetic mineralized PEEK implant at different mineralization times as described in Example 2.

[0023] Figure 2 These are scanning electron micrographs of the surfaces of the SPEEK implant, PVA-SPEEK implant, and HA-PVA-SPEEK implant described in Example 5.

[0024] Figure 3 This is a cross-sectional scanning electron micrograph of the strongly adhesive hydrogel coating described in Example 5.

[0025] Figure 4 This is an experiment to test the water contact angle on the surfaces of the SPEEK implant, PVA-SPEEK implant and HA-PVA-SPEEK implant described in Example 5.

[0026] Figure 5 This is a 90° peel test experiment of the strongly adhered hydrogel coating described in Example 5.

[0027] Figure 6 These are the biocompatibility test results of the SPEEK implant, PVA-SPEEK implant and HA-PVA-SPEEK implant surfaces described in Example 5.

[0028] Figure 7 These are scanning electron micrographs of the cell morphology on the surfaces of the SPEEK implant, PVA-SPEEK implant, and HA-PVA-SPEEK implant described in Example 5. DETAILED DESCRIPTION

[0029] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention.

[0030] The main purpose of the present invention is to solve the problems of poor biological activity on the surface of existing bone implants, weak adhesion of modified coatings, and poor osteogenesis, and to provide a method for preparing a biomimetic mineralized hydrogel coating with strong adhesion that is simple to operate, stable in process, and short in preparation time. The cross-linking property inside the hydrogel is enhanced by annealing treatment to form nanocrystalline domains and hydrogen bonds, thereby improving the adhesion performance of the hydrogel coating. The biomimetic mineralization method using calcium and phosphorus solutions is used to generate uniform hydroxyapatite on the surface of the hydrogel-coated bone implant.

[0031] The bone implants used in the following embodiments include titanium alloy materials, polyetheretherketone (PEEK) materials, magnesium alloy materials, zinc alloy materials or stainless steel materials.

[0032] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a biomimetic mineralized hydrogel coating with strong adhesion, comprising the following steps: The surface pre-treated bone implant is immersed in a polyvinyl alcohol (PVA) solution, and then subjected to a single freeze-thaw cycle, followed by an annealing treatment; wherein the surface pre-treatment of the bone implant includes grinding and surface activation treatment; The annealed bone implant is alternately immersed in a calcium solution and a phosphorus solution for surface mineralization treatment; the product after the surface mineralization treatment is then induced to become hydroxyapatite (HA); that is, a biomimetic mineralized hydrogel coating with strong adhesion is obtained on the surface of the bone implant. The surface of the prepared hydrogel coating is flat and uniform.

[0033] Among them, the surface mineralization treatment includes: The annealed bone implant is immersed in a phosphorus-containing solution for 2 to 4 minutes, then rinsed in deionized water for 10 to 15 seconds, immersed in a calcium-containing solution for 2 to 4 minutes, and rinsed in deionized water for 10 to 15 seconds, and the cycle is repeated 3 to 6 times.

[0034] The phosphorus-containing solution is a dipotassium hydrogen phosphate solution, and its concentration is 200-400 mM, preferably 300 mM; the calcium-containing solution is a calcium chloride solution, and its concentration is 300-600 mM, preferably 500 mM.

[0035] Before the surface mineralization treatment, the method also includes: immersing the annealed bone implant in a 1 M Tris buffer solution with a pH of 9 for 12 to 24 hours, and adjusting the pH inside the surface polyvinyl alcohol hydrogel to a pH of 9 that is most suitable for the growth of hydroxyapatite.

[0036] It should be noted that the phosphorus element was provided by potassium dihydrogen phosphate solution (300 mM) and the calcium element was provided by calcium chloride solution (500 mM) to induce a diffusion reaction on the surface of the hydrogel coating to generate a mineralized HA coating.

[0037] Specifically, the product after the surface mineralization treatment is induced to become hydroxyapatite, including: The bone implant after surface mineralization treatment is immersed in a calcium chloride solution for 24 to 36 hours to induce the surface mineralization product to become hydroxyapatite; the implant is mainly placed in a calcium chloride solution with a pH of 11 for 24 hours to obtain a uniformly distributed hydroxyapatite coating that is not affected by liquid disturbance.

[0038] Among them, the calcium-phosphorus ratio in hydroxyapatite is 1.60~1.75, and the particle size is 300~500 nm.

[0039] According to the present invention, the process of immersing the surface pretreated bone implant into the polyvinyl alcohol solution includes at least one immersion into the polyvinyl alcohol solution; wherein each immersion process is to immerse the surface pretreated bone implant into the polyvinyl alcohol solution, ensure that no bubbles are generated on the surface, and then take it out and place it in an oven for drying for 10 to 15 minutes; After the surface pre-treated bone implant is immersed in the polyvinyl alcohol solution, it is left to stand at room temperature for 0.5 to 1 hour.

[0040] The concentration of the polyvinyl alcohol solution is 10-12wt%.

[0041] A single freeze-thaw cycle includes: immersing the surface pretreated bone implant in a polyvinyl alcohol solution, freezing it at -20~-18°C for 8~10 hours, and then thawing it at room temperature for 2~4 hours.

[0042] The annealing temperature is 100-110°C, and the annealing time is 90-120 minutes. During the annealing process, the heating rate is 2°C / min, and after heat preservation, the material is cooled with the furnace.

[0043] In one embodiment, the specific preparation method of the PVA aqueous solution is as follows: 1.1) At room temperature, weigh 10 g of PVA powder (molecular weight 27.04522) and dissolve it in 90 mL of deionized water. Then, stir the mixture under magnetic stirring at 100 °C for 5 h until a transparent and uniform PVA aqueous solution is obtained.

[0044] 1.2) Centrifuge the prepared PVA aqueous solution at 5000 rpm for 20 minutes to eliminate the bubbles remaining in the solution.

[0045] In one embodiment, the specific preparation method of the strongly adherent PVA hydrogel coating is as follows: 2.1) Immerse the surface pretreated bone implant into the prepared PVA solution to ensure that no bubbles are generated on the surface. Take out the bone implant and dry it in an oven for 15 minutes, repeat the immersion, and let it stand for 0.5 hours. Then freeze the hydrogel-coated bone implant at -20 °C for 8 hours, thaw at room temperature for 3 hours, and air-dry for 8 hours to obtain a PVA hydrogel-coated bone implant with a smooth surface.

[0046] 2.2) The bone implant prepared above was annealed at 100°C for 1.5 hours. The specific annealing process parameters were: heating rate 2°C / min, heat preservation for 90 minutes, and cooling with the furnace.

[0047] In one embodiment, the specific preparation method of the strongly adherent biomimetic mineralized hydrogel coating is as follows: 3.1) The bone implant with strong adhesion hydrogel coating was immersed in 1 M Tris buffer solution with pH = 9 for 24 hours to adjust the pH value inside the hydrogel.

[0048] 3.2) The bone implant was sequentially immersed in 300 mM potassium hydrogen phosphate solution for 2 minutes, deionized water for 10 seconds, 500 mM calcium chloride solution for 2 minutes, and deionized water for 10 seconds. This cycle was repeated 5 times to control the thickness of the mineralized coating.

[0049] 3.3) The mineralized hydrogel-coated bone implant is immersed in a 500 mM calcium chloride solution at pH = 11 for 24 hours to allow the calcium phosphate formed by mineralization to mature into hydroxyapatite.

[0050] 3.4) Take out the mineralized hydrogel-coated bone implant from the solution and rinse it with deionized water three times to remove the residual calcium chloride on the surface.

[0051] The bone implant was immersed in a dipotassium hydrogen phosphate solution, and phosphate ions were evenly distributed on the surface and inside of the hydrogel through diffusion. After being immersed in a calcium chloride solution, the diffused calcium ions and the phosphate ions distributed in the hydrogel were attracted to each other under the action of electrostatics, and a chemical reaction occurred to form calcium phosphate precipitates, which subsequently matured into HA under pH=11.

[0052] The second aspect of the present invention provides a strongly adhesive biomimetic mineralized hydrogel coating, which is prepared by the above method, wherein the thickness of the strongly adhesive biomimetic mineralized hydrogel coating is 15-23 μm, and the interface toughness can reach 208.54 J / m 2 .

[0053] A third aspect of the present invention provides a use of a strongly adhesive biomimetic mineralized hydrogel coating in a bone implant.

[0054] It should be noted that the experimental methods used in the present invention are all conventional methods unless otherwise specified; the reagents and materials used are all commercially available unless otherwise specified.

[0055] Example 1 A method for preparing a strongly adherent biomimetic mineralized hydrogel coating on a PEEK implant surface comprises the following steps: Step 1: PEEK surface pretreatment: Use sandpaper to polish the surface of the PEEK sample, put the polished PEEK sample into deionized water, and ultrasonically clean it for 5 minutes to remove residual impurities; soak the cleaned PEEK sample in concentrated sulfuric acid for 1 minute to perform surface sulfonation treatment; quickly put the sulfonated PEEK sample into ice water for 1 minute to terminate the sulfonation reaction; The sulfonated PEEK sample was immersed in a 3 wt% sodium hydroxide solution for alkaline washing for 2 hours to further neutralize the residual sulfuric acid on the surface; it was ultrasonically cleaned with deionized water for 15 minutes to remove the residual sodium hydroxide and other impurities on the sample surface.

[0056] Step 2: Preparation of strongly adherent PVA hydrogel coating: At room temperature, weigh 10 g of PVA powder (molecular weight 27.04522) and dissolve it in 90 mL of deionized water; magnetically stir at 100 °C for 5 hours until a transparent and uniform PVA aqueous solution is formed; centrifuge the prepared PVA aqueous solution at 5000 rpm for 20 minutes to eliminate the bubbles remaining in the solution; immerse the pretreated sulfonated PEEK sample in the PVA solution to ensure that no bubbles are generated on the surface, take out the coated sulfonated PEEK sample, and divide the samples into 3 groups for different treatments.

[0057] Group 1: The coated sulfonated PEEK samples were taken out and placed at room temperature for 0.5 hours; Group 2: The coated sulfonated PEEK samples were taken out and placed in an oven to dry for 15 minutes, and then immersed in the PVA solution again and left to stand for 0.5 hours; The third group: The coated sulfonated PEEK sample was taken out, first placed in an oven to dry for 15 minutes, and then impregnated for the second time. The sample was placed in an oven to dry for 15 minutes again, and then impregnated for the third time, and then left to stand for 0.5 hours.

[0058] The three groups of sulfonated PEEK samples were frozen at -20°C for 8 hours after standing, then thawed at room temperature for 3 hours, and then air-dried for 8 hours to obtain PVA hydrogel coatings with smooth surfaces.

[0059] Step 3: Annealing: The three groups of hydrogel coatings were annealed at 100°C for 1.5 hours. The specific annealing process parameters were set as follows: heating rate 2°C / min, heat preservation for 90 minutes, and cooling with the furnace.

[0060] Step 4: Biomimetic mineralization treatment: The three groups of annealed strong adhesion hydrogel PEEK samples were soaked in 1M Tris buffer solution with pH = 9 for 24 hours to adjust the pH inside the hydrogel. The samples were soaked in 300 mM potassium dihydrogen phosphate solution for 2 minutes, deionized water for 10 seconds, 500 mM calcium chloride solution for 2 minutes, and deionized water for 10 seconds. Repeat the above cycle 5 times to control the thickness of the mineralized coating. The mineralized strong adhesion hydrogel PEEK sample was soaked in 500 mM calcium chloride solution with pH = 11 for 24 hours to allow the amorphous calcium phosphate formed by mineralization to mature into HA.

[0061] That is, strongly adhered biomimetic mineralized hydrogel coatings were obtained on the PEEK surfaces of the three groups.

[0062] Example 1 uses a single variable method to explore the effect of the number of times of immersion in a PVA solution on the coating thickness of a biomimetic mineralized hydrogel that is strongly adhered to the surface of a PEEK bone implant.

[0063] Example 2 A method for preparing a strongly adherent biomimetic mineralized hydrogel coating on a PEEK implant surface comprises the following steps: Step 1: PEEK surface pretreatment: Use sandpaper to polish the surface of the PEEK sample, put the polished PEEK sample into deionized water, and ultrasonically clean it for 5 minutes to remove residual impurities; soak the cleaned PEEK sample in concentrated sulfuric acid for 1 minute to perform surface sulfonation treatment; quickly put the sulfonated PEEK sample into ice water for 1 minute to terminate the sulfonation reaction; immerse the sulfonated PEEK sample in 3 wt% sodium hydroxide solution for alkaline washing for 2 hours to further neutralize the residual sulfuric acid on the surface; use deionized water to ultrasonically clean it for 15 minutes to remove the residual sodium hydroxide and other impurities on the sample surface.

[0064] Step 2: Preparation of strong adhesion PVA hydrogel coating: At room temperature, weigh 10 g of PVA powder (molecular weight 27.04522) and dissolve it in 90 mL of deionized water; stir magnetically at 100 °C for 5 hours until a transparent and uniform PVA aqueous solution is formed; centrifuge the prepared PVA aqueous solution at 5000 rpm for 20 minutes to eliminate the bubbles remaining in the solution; immerse the pretreated sulfonated PEEK sample in the PVA solution to ensure that no bubbles are generated on the surface; take out the coated sulfonated PEEK sample, place it in an oven to dry for 15 minutes, immerse it again, and let it stand for 0.5 hours. The sulfonated PEEK sample after standing was frozen at -20 °C for 8 hours, then thawed at room temperature for 3 hours, and air-dried for 8 hours to obtain a PVA hydrogel coating with a smooth surface.

[0065] Step 3: Annealing: The hydrogel coating is annealed at 100°C for 1.5 hours. The specific annealing process parameters are set as follows: heating rate 2°C / min, heat preservation for 90 minutes, and cooling with the furnace.

[0066] Step 4: Biomimetic mineralization treatment: The annealed strong adhesion hydrogel PEEK sample was immersed in 1 M pH = 9 Tris buffer solution for 24 hours to adjust the pH inside the hydrogel.

[0067] The pH-adjusted PEEK samples were subjected to the following soaking steps: Immersion in dipotassium hydrogen phosphate solution: PEEK samples were divided into four groups and immersed in 300 mM dipotassium hydrogen phosphate solution for 30 seconds, 1 minute, 2 minutes, and 3 minutes, respectively, to control the amount of phosphate diffusion in the early stage of mineralization; Deionized water cleaning: After soaking in potassium hydrogen phosphate solution, the four groups of samples were immersed in deionized water for 10 seconds to remove unreacted ions and residual solution; Calcium chloride solution immersion: The above four groups of samples were immersed in 500 mM calcium chloride solution for 30 seconds, 1 minute, 2 minutes and 3 minutes respectively to promote the diffusion and reaction of calcium ions on the surface of the hydrogel; Deionized water cleaning: After soaking in calcium chloride solution, soak the four groups of samples in deionized water for 10 seconds to ensure that excess calcium ions and solution residues are removed; Cycle repetition: The above immersion operation of potassium hydrogen phosphate, calcium chloride and deionized water is repeated 4 times for each group according to the immersion time of different groups to gradually control the thickness and uniformity of the mineralized coating.

[0068] The above four groups of mineralized strong adhesion hydrogel PEEK samples were immersed in 500 mM calcium chloride solution with pH=11 for 24 hours to allow the amorphous calcium phosphate formed by mineralization to mature into HA; the samples immersed in potassium hydrogen phosphate solution and calcium chloride solution for 30 seconds, 1 minute, 2 minutes and 3 minutes were marked as HA-PVA-SPEEK (30s), HA-PVA-SPEEK (1min), HA-PVA-SPEEK (2min) and HA-PVA-SPEEK (3min), respectively.

[0069] Example 2 uses a single variable method to explore the effect of a single immersion time of a mineralizing solution on the quality and distribution of a mineralized coating of a PEEK bone implant.

[0070] Example 3 A method for preparing a strongly adherent biomimetic mineralized hydrogel coating on the surface of a titanium alloy bone implant comprises the following steps: Step 1: Surface pretreatment of titanium alloy: Use sandpaper to polish the surface of the titanium alloy sample, and ultrasonically clean it for 5 minutes to remove residual impurities; plasma treat the cleaned titanium alloy sample for 5 minutes to increase the active groups on the surface.

[0071] Step 2: Preparation of strong adhesion PVA hydrogel coating: At room temperature, weigh 10 g of PVA powder (molecular weight 27.04522) and dissolve it in 90 mL of deionized water. Stir magnetically at 100 °C for 5 hours until a transparent and uniform PVA aqueous solution is formed. Centrifuge the prepared PVA aqueous solution (5000 rpm, 20 min) to eliminate the bubbles remaining in the solution; immerse the pretreated titanium alloy sample in the PVA solution to ensure that no bubbles are generated on the surface; take out the coated titanium alloy sample and divide the sample into 3 groups for different treatments.

[0072] Group 1: Take out the coated titanium alloy sample and place it at room temperature for 0.5 hours; Group 2: The coated titanium alloy samples were taken out and placed in an oven to dry for 15 minutes, and then the samples were immersed in the PVA solution again and left to stand for 0.5 hours; The third group: The coated titanium alloy samples were taken out, placed in an oven to dry for 15 minutes, and then impregnated for the second time. The samples were placed in an oven to dry for 15 minutes again, and then impregnated for the third time, and then left to stand for 0.5 hours.

[0073] The three groups of titanium alloy samples were frozen at -20°C for 8 hours after standing, then thawed at room temperature for 3 hours and air-dried for 8 hours to obtain a PVA hydrogel coating with a smooth surface.

[0074] Step 3: Annealing: The hydrogel coating is annealed at 100°C for 1.5 hours. The specific annealing process parameters are set as follows: heating rate 2°C / min, heat preservation for 90 minutes, and cooling with the furnace.

[0075] Step 4: Bionic mineralization treatment: The three groups of annealed strong adhesion hydrogel titanium alloy samples were immersed in 1 M Tris buffer solution with pH = 9 for 24 hours to adjust the pH inside the hydrogel. The samples were immersed in 300 mM potassium hydrogen phosphate solution for 2 minutes, deionized water for 10 seconds, 500 mM calcium chloride solution for 2 minutes, and deionized water for 10 seconds. Repeat the above cycle 5 times to control the thickness of the mineralized coating. The mineralized strong adhesion hydrogel titanium alloy sample was immersed in 500 mM calcium chloride solution with pH = 11 for 24 hours to mature the amorphous calcium phosphate formed by mineralization into HA.

[0076] That is, strongly adhered biomimetic mineralized hydrogel coatings were obtained on the surfaces of the three groups of titanium alloys.

[0077] Example 3 uses a single variable method to explore the effect of the number of immersion times in the PVA solution on the coating thickness of the biomimetic mineralized hydrogel that is strongly adhered to the surface of the titanium alloy bone implant.

[0078] Example 4 A method for preparing a strongly adherent biomimetic mineralized hydrogel coating on the surface of a titanium alloy bone implant comprises the following steps: Step 1: Surface pretreatment of titanium alloy: Use sandpaper to polish the surface of the titanium alloy sample, and ultrasonically clean it for 5 minutes to remove residual impurities; plasma treat the cleaned titanium alloy sample for 5 minutes to increase the active groups on the surface.

[0079] Step 2: Preparation of strong adhesion PVA hydrogel coating: At room temperature, weigh 10 g of PVA powder (molecular weight 27.04522) and dissolve it in 90 mL of deionized water. Stir magnetically at 100 °C for 5 hours until a transparent and uniform PVA aqueous solution is formed. Centrifuge the prepared PVA aqueous solution (5000 rpm, 20 min) to eliminate the bubbles remaining in the solution; immerse the pretreated titanium alloy sample in the PVA solution to ensure that no bubbles are generated on the surface; take out the coated titanium alloy sample, place it in an oven to dry for 15 minutes, immerse it again, and let it stand for 0.5 hours. The titanium alloy sample after standing was frozen at -20 °C for 8 hours, then thawed at room temperature for 3 hours, and air-dried for 8 hours to obtain a PVA hydrogel coating with a smooth surface.

[0080] Step 3: Annealing: The hydrogel coating is annealed at 100°C for 1.5 hours. The specific annealing process parameters are set as follows: heating rate 2°C / min, heat preservation for 90 minutes, and cooling with the furnace.

[0081] Step 4: biomimetic mineralization treatment: the strongly adherent hydrogel titanium alloy sample was immersed in 1 M Tris buffer solution with pH = 9 for 24 hours to adjust the pH inside the hydrogel; The titanium alloy sample after pH adjustment was subjected to the following soaking steps in sequence: Immersion in dipotassium hydrogen phosphate solution: The titanium alloy samples were divided into four groups and immersed in 300 mM dipotassium hydrogen phosphate solution for 30 seconds, 1 minute, 2 minutes, and 3 minutes, respectively, to control the amount of phosphate diffusion in the early stage of mineralization; Deionized water cleaning: After soaking in potassium hydrogen phosphate solution, soak the sample in deionized water for 10 seconds to remove unreacted ions and residual solution; Calcium chloride solution immersion: The above four groups of samples were immersed in 500 mM calcium chloride solution for 30 seconds, 1 minute, 2 minutes and 3 minutes respectively to promote the diffusion and reaction of calcium ions on the surface of the hydrogel; Deionized water cleaning: After soaking in calcium chloride solution, soak the sample in deionized water again for 10 seconds to ensure that excess calcium ions and solution residues are removed; Cycle repetition: The above immersion operation of potassium dihydrogen phosphate, calcium chloride and deionized water is repeated 4 times for each group according to the immersion time of different groups to gradually control the thickness and uniformity of the mineralized coating.

[0082] The above four groups of mineralized strong adhesion hydrogel titanium alloy samples were immersed in a 500 mM calcium chloride solution with a pH of 11 for 24 hours to allow the amorphous calcium phosphate formed by mineralization to mature into HA.

[0083] That is, strongly adhered biomimetic mineralized hydrogel coatings were obtained on the surfaces of the four groups of titanium alloys.

[0084] Example 4 uses a single variable method to explore the effect of a single immersion time in a mineralizing solution on the quality and distribution of a biomimetic mineralized hydrogel that is strongly adhered to the surface of a titanium alloy bone implant.

[0085] Example 5 A method for preparing a strongly adherent biomimetic mineralized hydrogel coating on the surface of a stainless steel bone implant comprises the following steps: Step 1: Stainless steel surface pretreatment: Use sandpaper to polish the surface of the stainless steel sample, and ultrasonically clean it for 5 minutes to remove residual impurities; plasma treat the cleaned stainless steel sample for 5 minutes to increase the active groups on the surface.

[0086] Step 2: Preparation of strongly adherent PVA hydrogel coating: At room temperature, weigh 10 g of PVA powder (molecular weight 27.04522) and dissolve it in 90 mL of deionized water; magnetically stir at 100 °C for 5 h until a transparent and uniform PVA aqueous solution is formed, and centrifuge the prepared PVA aqueous solution (5000 rpm, 20 min) to eliminate the bubbles remaining in the solution; immerse the pretreated stainless steel sample in the PVA solution to ensure that no bubbles are generated on the surface; take out the coated stainless steel sample and divide the samples into 3 groups for different treatments.

[0087] Group 1: Take out the coated stainless steel sample and place it at room temperature for 0.5 hours; Group 2: The coated stainless steel samples were taken out and placed in an oven to dry for 15 minutes, and then immersed in the PVA solution again and left to stand for 0.5 hours; The third group: The coated stainless steel samples were taken out, first placed in an oven to dry for 15 minutes, and then the second dipping operation was performed. The samples were placed in an oven to dry for 15 minutes again, and the third dipping operation was performed, and then left to stand for 0.5 hours. The three groups of stainless steel samples after standing were frozen at -20 ° C for 8 hours, then thawed at room temperature for 3 hours, and then air-dried for 8 hours to obtain a PVA hydrogel coating with a smooth surface.

[0088] Step 3: Annealing: The hydrogel coating is annealed at 100°C for 1.5 hours. The specific annealing process parameters are set as follows: heating rate 2°C / min, heat preservation for 90 minutes, and cooling with the furnace.

[0089] Step 4: Biomimetic mineralization treatment: The three groups of annealed strong adhesion hydrogel stainless steel samples were immersed in 1 M Tris buffer solution with pH = 9 for 24 hours to adjust the pH inside the hydrogel. The samples were immersed in 300 mM potassium hydrogen phosphate solution for 2 minutes, deionized water for 10 seconds, 500 mM calcium chloride solution for 2 minutes, and deionized water for 10 seconds. Repeat the above cycle 5 times to control the thickness of the mineralized coating. The mineralized strong adhesion hydrogel stainless steel sample was immersed in 500 mM calcium chloride solution with pH = 11 for 24 hours to mature the amorphous calcium phosphate formed by mineralization into HA.

[0090] That is, strongly adhered biomimetic mineralized hydrogel coatings were obtained on the stainless steel surfaces of the three groups.

[0091] Example 5 uses a single variable method to explore the effect of the number of immersion times in the PVA solution on the coating thickness, mineralized coating quality and distribution of the biomimetic mineralized hydrogel that is strongly adhered to the surface of the stainless steel bone implant.

[0092] Example 6 A method for preparing a strongly adherent biomimetic mineralized hydrogel coating on the surface of a stainless steel bone implant comprises the following steps: Step 1: Stainless steel surface pretreatment: Use sandpaper to polish the surface of the stainless steel sample, and ultrasonically clean it for 5 minutes to remove residual impurities; plasma treat the cleaned stainless steel sample for 5 minutes to increase the active groups on the surface.

[0093] Step 2: Preparation of strong adhesion PVA hydrogel coating: At room temperature, weigh 10 g of PVA powder (molecular weight 27.04522) and dissolve it in 90 mL of deionized water; stir magnetically at 100 °C for 5 h until a transparent and uniform PVA aqueous solution is formed, centrifuge the prepared PVA aqueous solution (5000 rpm, 20 min) to eliminate the bubbles remaining in the solution; take out the coated stainless steel sample, place it in an oven to dry for 15 minutes, dip it again, and let it stand for 0.5 hours. The stainless steel sample after standing was frozen at -20 °C for 8 hours, then thawed at room temperature for 3 hours, and air-dried for 8 hours to obtain a PVA hydrogel coating with a smooth surface.

[0094] Step 3: Annealing: The hydrogel coating is annealed at 100°C for 1.5 hours. The specific annealing process parameters are set as follows: heating rate 2°C / min, heat preservation for 90 minutes, and cooling with the furnace.

[0095] Step 4: Biomimetic mineralization treatment: The annealed strongly adherent hydrogel stainless steel sample was immersed in 1 M pH = 9 Tris buffer solution for 24 hours to adjust the pH inside the hydrogel.

[0096] The pH-adjusted stainless steel samples were subjected to the following soaking steps: Immersion in dipotassium hydrogen phosphate solution: The stainless steel samples were divided into four groups and immersed in 300 mM dipotassium hydrogen phosphate solution for 30 seconds, 1 minute, 2 minutes, and 3 minutes, respectively, to control the amount of phosphate diffusion in the early stage of mineralization; Deionized water cleaning: After soaking in potassium hydrogen phosphate solution, soak the sample in deionized water for 10 seconds to remove unreacted ions and residual solution; Calcium chloride solution immersion: The above four groups of samples were immersed in 500 mM calcium chloride solution for 30 seconds, 1 minute, 2 minutes and 3 minutes respectively to promote the diffusion and reaction of calcium ions on the surface of the hydrogel; Deionized water cleaning: After each immersion in calcium chloride solution, immerse the sample in deionized water for 10 seconds again to ensure that excess calcium ions and solution residues are removed; Cycle repetition: The above immersion operation of potassium hydrogen phosphate, calcium chloride and deionized water is repeated 4 times for each group according to the immersion time of different groups to gradually control the thickness and uniformity of the mineralized coating.

[0097] The above four groups of mineralized strong adhesion hydrogel stainless steel samples were immersed in 500 mM calcium chloride solution with pH = 11 for 24 hours to allow the amorphous calcium phosphate formed by mineralization to mature into HA.

[0098] That is, strongly adhered biomimetic mineralized hydrogel coatings were obtained on the stainless steel surfaces of the four groups.

[0099] Example 6 uses a single variable method to explore the effect of a single immersion time of a mineralizing solution on the coating quality and distribution of a biomimetic mineralized hydrogel that is strongly adhered to the surface of a stainless steel bone implant.

[0100] Example 7 A method for preparing a strongly adherent biomimetic mineralized hydrogel coating on a PEEK implant surface comprises the following steps: Step 1: PEEK surface pretreatment: PEEK surface pretreatment: Use sandpaper to polish the surface of the PEEK sample, put the polished PEEK sample into deionized water, and ultrasonically clean it for 5 minutes to remove residual impurities; soak the cleaned PEEK sample in concentrated sulfuric acid for 1 minute for surface sulfonation treatment; quickly put the sulfonated PEEK sample into ice water for 1 minute to terminate the sulfonation reaction; immerse the sulfonated PEEK sample in 3 wt% sodium hydroxide solution for alkaline washing for 2 hours to further neutralize the residual sulfuric acid on the surface; use deionized water to ultrasonically clean it for 15 minutes to remove the residual sodium hydroxide and other impurities on the sample surface. The PEEK sample after the above treatment is marked as SPEEK.

[0101] Step 2: Preparation of strong adhesion PVA hydrogel coating: At room temperature, weigh 10 g of PVA powder (molecular weight 27.04522) and dissolve it in 90 mL of deionized water; magnetically stir at 100 °C for 5 hours until a transparent and uniform PVA aqueous solution is formed, centrifuge the prepared PVA aqueous solution (5000 rpm, 20 min) to eliminate the bubbles remaining in the solution; immerse the pretreated SPEEK sample in the PVA solution to ensure that no bubbles are generated on the surface; take out the coated SPEEK sample, place it in an oven to dry for 15 minutes, immerse it again, and let it stand for 0.5 hours. The SPEEK sample after standing was frozen at -20 °C for 8 hours, then thawed at room temperature for 3 hours, and air-dried for 8 hours to obtain a PVA hydrogel coating with a smooth surface.

[0102] Step 3: Annealing: The hydrogel coating was annealed at 100°C for 1.5 hours. The specific annealing process parameters were set as follows: heating rate 2°C / min, heat preservation for 90 minutes, cooling with the furnace, and the sample after the above treatment was marked as PVA-SPEEK.

[0103] Step 4: Bionic mineralization treatment: The strongly adhesive hydrogel PEEK sample was immersed in 1 M Tris buffer solution with pH = 9 for 24 hours to adjust the pH inside the hydrogel; the sample was immersed in 300 mM potassium hydrogen phosphate solution for 2 minutes, deionized water for 10 seconds, 500 mM calcium chloride solution for 2 minutes, and then in deionized water for 10 seconds; the above cycle was repeated 5 times to control the thickness of the mineralized coating; the mineralized strongly adhesive hydrogel PEEK sample was immersed in 500 mM calcium chloride solution with pH = 11 for 24 hours to allow the amorphous calcium phosphate formed by mineralization to mature into HA, and the sample was labeled as HA-PVA-SPEEK.

[0104] Example 7 is a method for preparing a uniform, strongly adherent biomimetic mineralized hydrogel coating on the surface of a PEEK bone implant by freeze-thaw and biomimetic mineralization under the optimal experimental conditions: PEEK was oven-dried and re-immersed once after being coated with the PVA solution, and the single immersion time in the mineralizing solution was 2 minutes.

[0105] To illustrate the relevant properties of the composite material provided by the present invention, see Figures 1 to 7 As shown, the following is explained.

[0106] Figure 1 The scanning electron microscope images of the surface morphology of the biomimetic mineralized coating PEEK implant at different mineralization times described in Example 2. Figure 1It can be seen that the HA content on the surface of the HA-PVA-SPEEK (30s) sample is relatively low, and nucleation and growth only occur in a few areas; the HA content on the surface of the HA-PVA-SPEEK (1min) sample increases significantly, and in a few areas the surface is still unmineralized PVA hydrogel; the surface of the HA-PVA-SPEEK (2min) sample is evenly covered with a layer of HA, with uniform particle size and consistent coating thickness; a large amount of HA is generated on the surface of the HA-PVA-SPEEK (3min) sample, and island-like protrusions are formed in some areas, and the coating thickness is inconsistent. calcium With the extension of solution immersion time, the hydroxyapatite content on the coating surface gradually increased, indicating that controlling the mineralization time has an important influence on the structure and morphology of the coating.

[0107] Figure 2 The following are scanning electron micrographs of the surfaces of the SPEEK implant, PVA-SPEEK implant, and HA-PVA-SPEEK implant described in Example 5. Figure 2 It can be seen that the sulfonation treatment makes the surface of the SPEEK sample present an obvious porous structure; the PVA-SPEEK sample is covered with a hydrogel coating, and the surface becomes flat and dense, which enhances the adhesion and protection of the coating; the surface of the HA-PVA-SPEEK sample coating is evenly covered with hydroxyapatite, and the particle size is about 300-500 μm.

[0108] Figure 3 This is a cross-sectional scanning electron micrograph of the strong adhesion hydrogel coating described in Example 5, showing that its thickness is between 18-25 μm, confirming the stability and controllability of the preparation process.

[0109] Figure 4 This is a water contact angle test experiment on the surface of the SPEEK implant, PVA-SPEEK implant and HA-PVA-SPEEK implant described in Example 5. The test results show that: the SPEEK sample shows hydrophobic properties and a large contact angle; the PVA-SPEEK sample shows obvious hydrophilicity, and the hydrogel coating significantly reduces the water contact angle; the PVA-SPEEK-MIN sample still has a significant improvement in hydrophilicity compared to the SPEEK sample, which is conducive to cell adhesion and proliferation.

[0110] Figure 5 This is a 90° peel test of the strongly adherent hydrogel coating described in Example 5. Figure 5It can be seen that in the initial stage: the peeling force is relatively small and the displacement change is not obvious; in the middle stage: as the load increases, the hydrogel is gradually peeled off. When the unit peeling force reaches 225 N / m, the peeling force and adhesion force are balanced, and the corresponding stress value is the peeling force of the material; in the late stage: under the action of the load, the displacement gradually increases until the flexible backing is completely separated from the substrate, and the test ends. The calculated results show that the interface toughness of the hydrogel is 208.54 J / m 2 Therefore, the hydrogel coating has high interfacial toughness and adhesion properties.

[0111] Figure 6 and Figure 7 The following are the biocompatibility tests and cell morphology scanning electron microscopy images of the surfaces of the SPEEK implant, PVA-SPEEK implant and HA-PVA-SPEEK implant described in Example 5. Figure 6 It can be seen that the cell survival rate of samples in the same group increases with time. The control group has the highest cell survival rate and the best biocompatibility; the HA-PVA-SPEEK group is second; the PVA-SPEEK group and the SPEEK group are relatively poor. Figure 7 Cell morphology analysis showed that the porous structure on the surface of the SPEEK sample provided space for cells to spread; the PVA-SPEEK sample became dense after annealing treatment. Although the cell survival rate increased slightly compared with the SPEEK group, the overall biocompatibility was poor; the cells on the surface of the HA-PVA-SPEEK sample showed ductility, longer pseudopodia, and significantly improved biocompatibility.

[0112] In summary, the present invention provides a preparation method and application of a biomimetic mineralized hydrogel coating with strong adhesion, which includes the following steps: first, pretreating the surface of the bone implant to enhance the adhesion performance of the coating; immersing the pretreated bone implant in a configured polyvinyl alcohol (PVA) solution, taking it out after standing, repeating the above process, and then subjecting the obtained coating to a freeze-thaw cycle and annealing treatment, thereby obtaining a strongly adherent hydrogel coating on the surface of the bone implant. Next, by repeatedly immersing the bone implant in a calcium and phosphate solution, a mineralization reaction is induced on the surface of the hydrogel coating to form a uniformly distributed hydroxyapatite (HA) coating. The present invention has a simple process and is easy to operate. It can achieve stable hydrogel coating adhesion on the surface of a variety of bone implant materials, and the HA nanoparticles formed by mineralization can significantly improve the biocompatibility and osteogenic performance of the implant material. While providing a smooth and uniform appearance, the coating has excellent adhesion strength and mineralization uniformity, providing a new and efficient solution for the biomimetic repair of bone tissue defects.

[0113] The present invention describes preferred embodiments and their effects. However, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0114] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a biomimetic mineralized hydrogel coating with strong adhesion, characterized in that: The following steps are involved: The surface pretreated bone implant was immersed in a polyvinyl alcohol solution and then subjected to a single freeze-thaw cycle, followed by an annealing treatment; The annealed bone implant is alternately immersed in a calcium-containing solution and a phosphorus-containing solution to perform surface mineralization treatment; The product after surface mineralization treatment is then induced to become hydroxyapatite; That is, a biomimetic mineralized hydrogel coating with strong adhesion is obtained on the surface of the bone implant.

2. The method for preparing a biomimetic mineralized hydrogel coating with strong adhesion according to claim 1, characterized in that: Surface mineralization treatment includes: The annealed bone implant is immersed in a phosphorus-containing solution for 2 to 4 minutes, then rinsed in deionized water for 10 to 15 seconds, immersed in a calcium-containing solution for 2 to 4 minutes, and rinsed in deionized water for 10 to 15 seconds, and the cycle is repeated 3 to 6 times.

3. The method for preparing a biomimetic mineralized hydrogel coating with strong adhesion according to claim 2, characterized in that: The phosphorus-containing solution is a dipotassium hydrogen phosphate solution, and its concentration is 200-400 mM; the calcium-containing solution is a calcium chloride solution, and its concentration is 300-600 mM.

4. The method for preparing a biomimetic mineralized hydrogel coating with strong adhesion according to claim 1, characterized in that: The product after surface mineralization treatment is induced to become hydroxyapatite, including: The surface mineralized bone implant is immersed in a calcium chloride solution for 24 to 36 hours to induce the surface mineralized product to become hydroxyapatite; Among them, the calcium-phosphorus ratio in hydroxyapatite is 1.60~1.75, and the particle size is 300~500 nm.

5. The method for preparing a biomimetic mineralized hydrogel coating with strong adhesion according to claim 1, characterized in that: Before the surface mineralization treatment, the method further includes: immersing the annealed bone implant in a 1 M Tris buffer solution with a pH of 9 for 12 to 24 hours.

6. The method for preparing a biomimetic mineralized hydrogel coating with strong adhesion according to claim 1, characterized in that: Immersing the surface pretreated bone implant in the polyvinyl alcohol solution includes at least one immersion in the polyvinyl alcohol solution; wherein each immersion process is to immerse the surface pretreated bone implant in the polyvinyl alcohol solution, ensure that no bubbles are generated on the surface, take it out and place it in an oven to dry for 10 to 15 minutes; The bone implant after surface pretreatment is immersed in a polyvinyl alcohol solution and then left to stand at room temperature for 0.5 to 1 hour; wherein the concentration of the polyvinyl alcohol solution is 10 to 12 wt %.

7. The method for preparing a biomimetic mineralized hydrogel coating with strong adhesion according to claim 1, characterized in that: A single freeze-thaw cycle includes: immersing the surface pretreated bone implant in a polyvinyl alcohol solution, freezing it at -20 to -18°C for 8 to 10 hours, and then thawing it at room temperature for 2 to 4 hours.

8. The method for preparing a biomimetic mineralized hydrogel coating with strong adhesion according to claim 1, characterized in that: The annealing temperature is 100-110°C and the annealing time is 90-120 minutes.

9. A biomimetic mineralized hydrogel coating with strong adhesion, characterized in that: The method is prepared by any one of claims 1 to 8, wherein the thickness of the strongly adhesive biomimetic mineralized hydrogel coating is 15-23 μm, and the interface toughness can reach 208.54 J / m 2 .

10. Use of the strongly adhesive biomimetic mineralized hydrogel coating according to claim 9 in bone implants.

Citation Information

Patent Citations

  • High-strength high-flexibility mineralized water gel as well as preparation method and application

    CN107778416A

  • Enzymatic mineralization polyacryloyl glycinamide hydrogel and preparation method thereof

    CN112625158A

  • Preparation method of high-adhesion analgesic hydrogel microneedle patch and microneedle patch

    CN114432275A

  • Production method of body paper for vacuum aluminum plating

    CN108035193A

  • Preparation and application of stain-resistant coating on surface of implantable sensor

    CN108295320A

Cited By

  • Multi-dimensional bionic scaffold with space-time synergistic osteogenesis function and preparation method

    CN120754327A